Enhancing the hydrogen tolerance of La0.6Ca0.4Co0.2Fe0.8O3–d oxygen transport membranes with the substitution of 10 % Mn at the B site for plasma assisted CO2 conversion - Aasir Rashid; Moritz Thiem; Merle Wellmann; Marc Bresser; Olaf Lindemann; Katharina-Sophia Wiegers; Jan Philipp Hofmann; Andreas Schulz; Armin Feldhoff; Anke Weidenkaff; Marc Widenmeyer (Open Ceramics)
The tendency of mixed ionic electronic conducting (MIEC) materials to be highly selective towards oxygen allows for their use as oxygen transport membranes (OTMs). To be used as OTMs in plasma assisted CO2 conversion and H2 utilisation applications, requires high oxygen permeability, structural stability against reducing atmospheres (such as CO2, CO, H2, etc.) and suitable mechanical properties. La0.6Ca0.4Co1–xFexO3–d (LCCF) has already shown excellent tolerance against CO2 and recently, in our previous work, its specific variant, La0.6Ca0.4Co0.2Fe0.8O3–d (LCCF_6428) showcased hydrogen tolerance for upto 25 hours at 600 °C. In this work, we aim to further improve the hydrogen tolerance of LCCF_6428 by the introduction of strong Mn4+-O bonds into the material structure. To achieve this, 10 % Fe was substituted with manganese (Mn) at the B site of LCCF_6428. The resulting composition La0.6Ca0.4Co0.2Fe0.7Mn0.1O3–d (LCCF_64271) was chosen and synthesized with ultrasonic spray synthesis (USS). The presence of strong Mn4+-O bonds led to a two-fold increase in the hydrogen tolerance of the membrane material with respect to LCCF_6428 with a slight 5 % decrease in oxygen permeability.